Local Wisdom Digital Storytelling to Foster Cultural Literacy and Communicative Competence in EFL Contexts - Aisyah Ashar; Aqzhariady Khartha; Syarif Hidayat Nasir (Universitas Muhammadiyah Tangerang, 2026)
In the changing digital age, learning English faced important challenges in linking teaching materials with students' cultural backgrounds. Traditional methods often focused on grammar accuracy rather than meaningful communication and cultural understanding. This approach led to lower student engagement and weaker communication skills. This study examined how local wisdom-based digital storytelling served as a fresh teaching method in English classrooms at SMA Negeri 1 Kolaka in Southeast Sulawesi, Indonesia. The research used a qualitative case study method to explore how two experienced English teachers incorporated local cultural values into digital storytelling activities. It also looked at how this affected twenty eleventh-grade students' cultural knowledge and communication skills. The data were gathered over three months through detailed interviews with teachers and selected students, classroom observations, and thorough analysis of lesson plans and student-created digital stories. The findings showed that culturally relevant digital storytelling greatly increased students' engagement, cultural identity, and language skills by linking English learning to their social realities. Teachers effectively included local stories from Tolaki and Bugis traditions in digital media projects. This method deepened cultural understanding while improving students' communication abilities. However, the findings also revealed challenges such as limited technology, students' initial reluctance to embrace local cultural content, and the need for teachers to receive special training in digital tools. This research contributed to the field by providing a solid framework for blending local wisdom with digital technology in language teaching. It offered practical ideas for creating culturally responsive teaching that improved both cultural knowledge and communication skills in secondary English classrooms.